Location Characteristics of the New Country Capital in East Kalimantan Province - Astinana Yuliarti; Syamani D Ali; Karnanto Hendra Murliawan; Abd Rahman; Ogie Elian Aziz Arief; Muhammad Naufal Muza; Sahrul Rinaldi; Rizky Nurita Anggraini; Rosalina Kumalawati (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
The relocation of the national capital has been carried out by several countries for various reasons. This study aimed to determine the characteristics of the location of the nation’s capital city in East Kalimantan Province. The research was conducted in two regencies, 3 sub-districts, and 4 sub-districts. Penajam Paser Utara District includes Babulu and Sepaku Districts, while Kutai Kartanegara District includes Muara Jawa District. The data used in this study is secondary data from the study literature. The findings from the study are that in West Babulu Village there is a network of arterial roads and local roads. Pemaluan Village, Sepaku Village, and Teluk Dalam Village have a network of local roads and other roads. North Panajam Paser Regency has 3 watersheds and Kutai Kartanegara Regency has 2 watersheds in total there are 5 watersheds. Meeting water needs apart from river water can also be from dams. In 2023, it is estimated that the Nation Capital's water needs will reach 16,500 liters/second, with the needs of surrounding districts in that year reaching 27,232 liters/second. In line with the development of the city and its facilities, the need for water will increase, so the nation’s capital city requires alternative sources of additional water. Topographic conditions seen from elevation, slope, and landform, there are several areas that need to be maintained as protected areas or city green open spaces (RTH), urban forests, which can also function as educational or tourism facilities for Capital cities in order to protect areas that are underneath